Composition

JP2025027509APending Publication Date: 2025-02-28AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023132287
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、テトラフルオロエチレン系ポリマーと所定のフィラーとを含み、分散性に優れた組成物が提供される。かかる組成物からは、機械的特性、耐熱性に優れ、線膨張係数、誘電率及び誘電正接が低く、特に電気絶縁性を維持しつつ熱伝導性に優れ表面粗さが小さいシート等の成形物を形成でき、放熱材料として好適に使用できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027509000001
    Figure 2025027509000001
Patent Text Reader

Abstract

To provide a composition containing a tetrafluoroethylene polymer, enabling the formation of moldings such as sheets that exhibit superior mechanical properties and heat resistance, deliver low linear expansion coefficients, dielectric constants and dielectric loss tangents, demonstrate superior thermal conductivity while maintaining electrical insulating properties, and offer low surface roughness, wherein the composition is suitably usable as a heat-dissipating material.SOLUTION: A composition comprises tetrafluoroethylene polymer particles, a first filler that is a nitride, a second filler that is a metal or a metal oxide, and a third filler that is a metal or a metal oxide. The average particle diameter D1 of the first filler, the average particle diameter D2 of the second filler, and the average particle diameter D3 of the third filler satisfy the relationship D1>D2>D3, and the ratio of the average particle diameter of the tetrafluoroethylene polymer particles to D3 is 2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition comprising a tetrafluoroethylene-based polymer and a plurality of selected fillers. [Background technology]

[0002] Thermal interface materials (hereinafter, also referred to as "TIM") are used as heat dissipation materials to dissipate large amounts of heat generated from electronic components such as computer chips (CPUs), video graphics arrays, servers, game consoles, smartphones, and LED boards, as well as semiconductor modules including power semiconductors used in inverters and converters in electric vehicles and power transmission systems. TIMs typically have the role of transferring excess heat from electronic components to a heat diffusion section, and then transferring the heat to a heat sink. Conventionally, phase change materials such as paraffin wax, grease-like materials, and elastomer tapes have been used as TIMs because they can spread in a very thin layer and provide intimate contact between adjacent surfaces. However, these materials have problems such as poor heat resistance (thermal stability) and are prone to performance degradation. In order to improve the thermal conductivity of the resin material and obtain a heat dissipation material applicable to TIM, various heat conductive fillers have been blended into the resin. Patent Document 1 proposes a heat dissipation sheet containing a resin binder and two types of inorganic particles with different particle sizes, with each inorganic particle present in a predetermined amount in a predetermined region in the thickness direction from one surface of the entire thickness. Patent Document 2 proposes a heat conductive resin composition in which a predetermined amount of scaly boron nitride with a predetermined particle size and three types of heat conductive fillers with different particle sizes are blended into the resin. Patent Document 3 proposes an insulating resin sheet containing a predetermined amount of inorganic filler that shows a maximum peak in the 15-25 μm region in the volume frequency particle size distribution and has a particle size of 40-55 μm that is 95% of the cumulative volume frequency, and a binder resin. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 065146 [Patent Document 2] Patent Publication No. 2022-026651 [Patent Document 3] JP 2023-033211 A Summary of the Invention [Problem to be solved by the invention]

[0004] On the other hand, tetrafluoroethylene-based polymers used as resin components of such thermally conductive materials and heat dissipating materials have excellent mechanical properties, heat resistance, and electrical properties (linear expansion coefficient, dielectric constant, dielectric tangent, etc.), but on the other hand, they have low surface tension and low affinity with other components, and therefore tend to induce aggregation of the thermally conductive components, not only reducing the thermal conductivity of the molded product but also roughening the surface of the molded product.

[0005] The present inventors have discovered that a composition containing tetrafluoroethylene-based polymer particles, a nitride filler, and a plurality of fillers which are a specified metal or its oxide, in which the ratio of the average particle size of each filler to the average particle size of the tetrafluoroethylene-based polymer particles satisfies a specified relationship, has excellent dispersibility, and molded products thereof have excellent mechanical properties and heat resistance, a low linear expansion coefficient, a low dielectric constant and a low dielectric tangent, and in particular, excellent thermal conductivity while maintaining electrical insulation, and can also have reduced surface roughness, thereby completing the present invention. It is an object of the present invention to provide such a composition, and a heat dissipating material containing said composition. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A composition comprising particles of a tetrafluoroethylene-based polymer, a first filler which is a nitride, a second filler which is a metal or an oxide thereof, and a third filler which is a metal or an oxide thereof, wherein an average particle size D1 of the first filler, an average particle size D2 of the second filler, and an average particle size D3 of the third filler satisfy the relationship D1>D2>D3, and the ratio of the average particle size of the particles of the tetrafluoroethylene-based polymer to D3 is 2 or less. [2] The composition of [1], wherein the ratio of the average particle diameter D2 to the average particle diameter D3 is greater than 2. [3] The composition according to [1] or [2], wherein the tetrafluoroethylene-based polymer is a heat-fusible tetrafluoroethylene-based polymer having an oxygen-containing polar group. [4] The composition according to any one of [1] to [3], wherein the average particle size of the particles of the tetrafluoroethylene polymer is 0.1 to 6 μm. [5] The composition according to any one of [1] to [4], wherein the first filler is an aggregate of scaly primary particles of boron nitride, and the average particle diameter D1 of the aggregate is 25 to 75 μm. [6] The composition according to any one of [1] to [5], wherein the second filler is aluminum oxide and the average particle size D2 is 10 to 40 μm. [7] The composition according to any one of [1] to [6], wherein the third filler is aluminum oxide and the average particle size D3 is less than 10 μm. [8] The composition according to any one of [1] to [7], wherein the second filler and the third filler are both spherical. [9] The composition according to any one of [1] to [8], wherein the content of the tetrafluoroethylene-based polymer particles is 10 to 30 volume %, the content of the first filler is 5 to 30 volume %, the content of the second filler is 50 to 80 volume %, and the content of the third filler is 5 to 30 volume %, relative to the total amount of the tetrafluoroethylene-based polymer particles, the first filler, the second filler, and the third filler.

[10] The composition according to any one of [1] to [9], further comprising a liquid dispersion medium.

[11] A heat dissipating material containing any one of the compositions according to [1] to

[10] .

[12] A method for producing a molded article, comprising extruding the composition according to any one of [1] to

[10] or disposing it on a surface of a substrate to obtain a molded article containing the tetrafluoroethylene-based polymer, the first filler, the second filler, and the third filler.

[13] A molded article comprising a tetrafluoroethylene-based polymer, a first filler which is a nitride, a second filler which is a metal or an oxide thereof, and a third filler which is a metal or an oxide thereof, wherein an average particle size D1 of the first filler, an average particle size D2 of the second filler, and an average particle size D3 of the third filler satisfy the relationship D1>D2>D3.

[14] A molded article according to

[13] , having a thickness of 100 μm or more.

[15] A molded product according to

[13] or

[14] , having a surface roughness Rz of 25 μm or less.

[16] Any of the molded articles

[13] to

[14] , having a thermal conductivity of 5 W / m K or more. Effect of the Invention

[0007] According to the present invention, there is provided a composition containing a tetrafluoroethylene-based polymer and a specific filler and having excellent dispersibility. From such a composition, a molded product such as a sheet having excellent mechanical properties, heat resistance, a low linear expansion coefficient, a low dielectric constant and a low dielectric tangent, and particularly excellent thermal conductivity while maintaining electrical insulation and small surface roughness can be formed, and the composition can be suitably used as a heat dissipation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The following terms have the following meanings: "Average particle size (D50)" is the cumulative 50% volumetric diameter of a particle or filler determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, the total volume of the particle or filler group is set as 100%, a cumulative curve is calculated, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles or fillers is determined by dispersing the particles or fillers in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."

[0009] The composition of the present invention (hereinafter also referred to as "the composition") comprises particles (hereinafter also referred to as "F particles") of a tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer"), a first filler (hereinafter also referred to as "first filler") which is a nitride, a second filler (hereinafter also referred to as "second filler") which is a metal or its oxide, and a third filler (hereinafter also referred to as "third filler") which is a metal or its oxide, wherein an average particle diameter D1 of the first filler, an average particle diameter D2 of the second filler, and an average particle diameter D3 of the third filler satisfy the relationship D1>D2>D3, and the ratio of the average particle diameter of the tetrafluoroethylene-based polymer particles to D3 is 2 or less.

[0010] The composition has excellent dispersibility, has high physical properties of the F polymer and each filler, has excellent mechanical properties and heat resistance, has a low linear expansion coefficient, dielectric constant and dielectric loss tangent, and is particularly excellent in thermal conductivity while maintaining electrical insulation, and is easy to form molded products such as sheets with small surface roughness. The reason for this is not necessarily clear, but is thought to be as follows.

[0011] F polymer has low affinity with other materials. Therefore, if the inorganic filler is in the form of fine particles, the fillers tend to aggregate with each other in the composition, making it difficult to exhibit the physical properties, and also reducing the mechanical properties of the molded product obtained from it. In this composition, three types of inorganic fillers with stepwise different average particle sizes are used in combination. That is, by using a first filler, which is a nitride and has high thermal conductivity, and two fillers (a second filler and a third filler) with different average particle sizes, which are metals or their oxides and have a smaller average particle size than the first filler, in combination, it is considered that the interaction between the three is promoted, a dense thermal conductive path is formed, and the aggregation is suppressed by the two different fillers. In addition, by using F particles having a predetermined average particle size for the third filler, which has the smallest average particle size, an increase in the surface roughness of the molded product due to excessive surface exposure of the first filler to the third filler is suppressed, and dense packing of the F polymer between the first filler to the third filler is further promoted. And, it is considered that the interaction between each filler and the F polymer in the composition is promoted, and the uniform dispersibility of the composition is improved. In a molded product such as a sheet formed from such a composition, the gaps filled by the first filler are efficiently and densely filled with the second and third fillers, which facilitates the formation of high-grade filler paths, and is believed to improve the heat resistance, linear expansion coefficient, and electrical properties of the molded product, particularly the thermal conductivity, while maintaining electrical insulation. Furthermore, the contact interface between the F polymer and the first, second, and third fillers is enlarged, which is believed to improve the mechanical properties of the molded product, such as bending strength. This tendency becomes more pronounced when the ratio of the average particle diameter D2 to the average particle diameter D3 of the F polymer, the first filler, the second filler and the third filler in the present composition is more than 2.

[0012] The F polymer in the present invention is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE units"). One type of F polymer may be used, or two or more types may be used. The F polymer may be either heat-fusible or non-heat-fusible, but at least one type of F polymer is preferably heat-fusible. Here, the heat-fusible polymer means a polymer that has a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The melting temperature of the thermally meltable F polymer is preferably 180° C. or higher, more preferably 200° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. In this case, the composition is likely to have excellent processability, and a molded product formed from the composition is likely to have excellent heat resistance.

[0013] The glass transition point of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition point of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.

[0014] F polymer is preferably polytetrafluoroethylene (PTFE), a polymer containing TFE units and units based on ethylene (ETFE), a polymer containing TFE units and units based on propylene, a polymer containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), a polymer containing TFE units and units based on hexafluoropropylene (FEP), more preferably PFA and FEP, and even more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.

[0015] The F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl- or carbonyl-containing group, and even more preferably has a carbonyl-containing group. In this case, the F polymer easily interacts with the first filler, the second filler, and the third filler, and the composition is easily excellent in dispersibility. In addition, the composition is easily used to obtain a molded product such as a sheet having a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and excellent heat resistance and thermal conductivity. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), a formyl group, a halogenoformyl group, a urethane group (-NHC(O)O-), a carbamoyl group (-C(O)-NH2), a ureido group (-NH-C(O)-NH2), an oxamoyl group (-NH-C(O)-C(O)-NH2) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6 The number of oxygen-containing polar groups per unit is preferably 50 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.

[0016] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.

[0017] The F polymer is preferably a polymer having a carbonyl group-containing group containing TFE units and PAVE units, more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in this order, 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol%, based on all units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644.

[0018] In the present invention, the average particle size (D50) of the F particles is preferably 0.1 μm or more, more preferably 0.3 μm or more. The D50 of the F particles is preferably 25 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less. The D50 of the F particles is more preferably 0.1 to 6 μm. In this case, the composition is likely to have excellent dispersibility and processability. Furthermore, from the composition, a molded product such as a sheet having a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and excellent heat resistance and thermal conductivity can be easily obtained. The F particles may be in the form of non-hollow particles or pellets. The specific surface area of ​​F particles is 1 to 25 m 2 / g is preferable, and 3 to 15m 2 / g is more preferred.

[0019] The F particles are particles containing an F polymer, and preferably consist of an F polymer. The F particles are more preferably particles of a heat-fusible F polymer having an oxygen-containing polar group and a melting temperature of 100 to 320° C. In this case, the above-mentioned mechanism of action is more effectively exerted, and aggregation of the F particles is also easily suppressed. The F particles may contain a resin or an inorganic compound other than the F polymer, may form a core-shell structure with an F polymer as the core and a resin other than the F polymer or an inorganic compound as the shell, or may form a core-shell structure with an F polymer as the shell and a resin other than the F polymer or an inorganic compound as the core. Here, examples of the resin other than the F polymer include aromatic polyester, polyamideimide, polyimide, and maleimide, and examples of the inorganic compound include silica and boron nitride.

[0020] One type of F particle may be used, or two or more types of F particles may be used. The F particles may be mixed with particles of a non-thermofusible tetrafluoroethylene polymer. As the F particles, particles of a heat-fusible F polymer having a melting temperature of 100 to 325°C are preferred, particles of a heat-fusible F polymer having a melting temperature of 180 to 320°C and having an oxygen-containing polar group are more preferred, and as particles of a non-thermofusible tetrafluoroethylene polymer, particles of a non-thermofusible PTFE are preferred. In this case, the aggregation suppression effect of the particles of the heat-fusible F polymer and the retention effect of the fibrillation of the non-thermofusible tetrafluoroethylene polymer are balanced, and the dispersibility of the composition is easily improved. In addition, the electrical properties of the non-thermofusible tetrafluoroethylene polymer are easily expressed to a high degree in the molded product obtained therefrom.

[0021] The first filler contained in the present composition includes a boron nitride filler, an aluminum nitride filler, and a silicon nitride filler. Specific examples of boron nitride fillers include the "HP-40MF" series, "HP-40J" series (both manufactured by JFE Mineral Co., Ltd.), the "UHP" series (manufactured by Showa Denko K.K.), and the "GP" and "HGP" grades of the "Denka Boron Nitride" series (manufactured by Denka Co., Ltd.). Specific examples of aluminum nitride fillers include the "High Purity Aluminum Nitride" series (Tokuyama Corporation) and the "Toyal Tech Filler TFZ" series (manufactured by Toyo Aluminium Co., Ltd.). Specific examples of silicon nitride fillers include the "Denka Silicon Nitride" series (manufactured by Denka Co., Ltd.) and the "UBE Silicon Nitride" series (manufactured by UBE Co., Ltd.). The first filler may be used alone or in combination of two or more kinds. Among them, it is more preferable that the first filler is a boron nitride filler.

[0022] The shape of the first filler is preferably non-spherical, more preferably scale-like or columnar. In this case, it is considered that the first filler is likely to have a card-house structure in the present composition and in the molded product such as a sheet formed from the present composition, and is likely to form a heat conduction path. As a result, the present composition is excellent in dispersibility, and the molded product is likely to be excellent in thermal conductivity (thermal conductivity rate) and low linear expansion. The D50 of the first filler is preferably 20 μm or more, more preferably 25 μm or more, and is preferably 100 μm or less, more preferably 75 μm or less. The aspect ratio of the first filler is preferably greater than 1, more preferably equal to or greater than 2, and even more preferably equal to or greater than 5. The aspect ratio is preferably 10,000 or less. The true density of the first filler is 1 to 7 g / cm 3 is preferred. The bulk density of the first filler is 0.1 to 6.0 g / cm 3 is preferred. The first filler preferably has a compressive strength of 30 to 200 MPa, as measured according to ASTM D 3102-78.

[0023] The surface of the first filler may be surface-treated with a silane coupling agent. Examples of the silane coupling agent include vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-isocyanatepropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, p-styryltrimethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, N-2-(aminomethyl)-8-aminooctyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0024] Among them, the first filler is preferably an aggregate in the form of a mass formed by agglomeration of scaly primary particles of boron nitride, and the average particle diameter D1 of such aggregates is preferably 25 to 75 μm, more preferably 30 to 60 μm. Here, the ratio of the major axis to the thickness of the primary particles of boron nitride is preferably 5 to 10 on average. Also, it is more preferable that such aggregates are sintered bodies obtained by firing boron carbide at a nitrogen partial pressure of 5 kPa or more and a firing temperature of 1800 to 2200° C.

[0025] Examples of metals or oxides thereof constituting the second filler and the third filler contained in the present composition include metals such as silver and copper; and metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide. The second filler and the third filler may each be used alone or in combination of two or more kinds. The second and third fillers may be different or the same, preferably the same, and more preferably both are aluminum oxide, in which case the composition can be easily used to obtain a molded product having excellent electrical properties, low linear expansion, and thermal conductivity.

[0026] The shape of the second filler and the third filler may be any of spherical, needle-like (fibrous), and plate-like. From the viewpoint of further improving the thermal conductivity of molded products such as sheets obtained from the present composition, and of heat dissipation materials such as TIMs containing the present composition, which will be described later, it is preferable that the second filler and the third filler are both spherical. Here, "spherical" may be elliptical, but is preferably substantially spherical. "Substantially spherical" means that, when the filler is observed with a scanning electron microscope (SEM), the ratio of particles having a minor axis to major axis ratio of 0.7 or more accounts for 95% or more. In this case, the composition is likely to have excellent dispersibility and processability. In addition, in a molded product such as a sheet formed from the composition, the first filler, the second filler, and the third filler, which have different average particle sizes, are efficiently arranged, and the fillers are densely packed while suppressing aggregation of each filler, so that a heat conduction path is easily formed, and a molded product such as a sheet is easily obtained that has excellent mechanical properties, a low linear expansion coefficient, a low dielectric constant, and a low dielectric tangent, and in particular, excellent thermal conductivity while maintaining electrical insulation, and has a small surface roughness.

[0027] The average particle size D2 of the second filler is preferably 10 to 40 μm. D2 is more preferably 14 μm or more, and even more preferably 18 μm or more. D2 is more preferably 36 μm or less, and even more preferably 32 μm or less. The average particle size D3 of the third filler is preferably less than 10 μm, more preferably 8 μm or less, and even more preferably 5 μm or less, and is preferably 0.1 μm or more. The third filler may be an aggregate of primary particles of a metal or its oxide. When the third filler is an aggregate, the average particle size of the aggregate is preferably less than 10 μm, and the aggregate is more preferably a sintered body obtained by firing.

[0028] The true density of the second filler and the third filler is 1 to 7 g / cm 3 is preferred. The bulk density of the second filler and the third filler is 0.1 to 6 g / cm 3is preferred. The second and third fillers preferably have a compressive strength of 30 to 200 MPa, as measured according to ASTM D 3102-78.

[0029] The second and third fillers are preferably non-surface-treated fillers, from the viewpoint of forming filler paths by more densely filling gaps packed with the first filler in a molded product such as a sheet, and of highly expressing the physical properties of the second and third fillers themselves to further improve the thermal conductivity, etc., of the molded product. Note that "surface treatment" includes surface treatment using an organic surface treatment agent such as a silane coupling agent, an inorganic surface treatment agent such as an inorganic acid, or a physical operation.

[0030] In this composition, the average particle diameter D1 of the first filler, the average particle diameter D2 of the second filler, and the average particle diameter D3 of the third filler satisfy the relationship D1>D2>D3, and the ratio of the average particle diameter (D50) of the F particles to D3 is 2 or less. In the present composition, it is preferable that the first filler has a non-spherical shape (scale or columnar), and the second filler and the third filler have a spherical shape. That is, the first filler is an aggregate of scaly primary particles of boron nitride, and the average particle diameter D1 of the aggregate is preferably 25 to 75 μm. The second filler is preferably spherical aluminum oxide having an average particle size D2 of 10 to 40 μm. D2 is more preferably 14 μm or more, and even more preferably 18 μm or more. D2 is more preferably 36 μm or less, and even more preferably 32 μm or less. Furthermore, the third filler is preferably spherical aluminum oxide, and the average particle size D3 is preferably less than 10 μm. D3 is more preferably 8 μm or less, and even more preferably 5 μm or less. D3 is preferably 0.1 μm or more. Furthermore, D2 relative to D3 is preferably greater than 2, and more preferably 5 or greater. The ratio of the average particle size (D50) of the F particles to D3 is not more than 2, and preferably not more than 1.5. The ratio of the average particle size (D50) of the F particles to D3 is preferably not less than 0.2, and more preferably not less than 0.5.

[0031] In such a molded product such as a sheet formed from the composition of the present invention, the above-mentioned assumed mechanism is more clearly expressed, and the first filler, the second filler, and the third filler, which have different average particle sizes, are efficiently arranged, and the fillers are densely packed while suppressing aggregation of each filler, making it easy to form a heat conduction path, and it is easy to obtain a molded product such as a sheet, which has excellent mechanical properties, a low linear expansion coefficient, a low dielectric constant, and a low dielectric tangent, and in particular, excellent thermal conductivity while maintaining electrical insulation, and has reduced surface roughness.

[0032] In the present composition, it is preferable that the content of the F particles is 10 to 30 volume %, the content of the first filler is 5 to 30 volume %, the content of the second filler is 50 to 80 volume %, and the content of the third filler is 5 to 30 volume %, relative to the total amount of the F particles, the first filler, the second filler, and the third filler. When the volume concentration is within this range, the composition is likely to have excellent dispersibility. In addition, the composition is likely to produce a molded product such as a sheet that has a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and in particular has excellent thermal conductivity while maintaining electrical insulation, and has small surface roughness.

[0033] The thermal conductivity of each of the first, second and third fillers contained in the composition alone is preferably 20 W / m K or more, and more preferably 30 W / m K or more. There is no particular upper limit to the thermal conductivity of each of the first, second and third fillers alone, and the higher the better, but in general, it is preferably 3000 W / m K or less, and more preferably 2500 W / m K or less.

[0034] The present composition may further contain other resins different from the F polymer, as long as the effects of the present invention are not impaired. Such other resins may be contained in the present composition as non-hollow particles, or, when the present composition contains a liquid dispersion medium described below, may be dissolved or dispersed in the liquid dispersion medium. Examples of other resins include fluororesins other than F polymers, polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. The other resin is preferably a tetrafluoroethylene polymer other than the F polymer, an aromatic polymer, and more preferably at least one aromatic imide polymer selected from the group consisting of aromatic polyimide, aromatic polyamic acid, aromatic polyamideimide, and a precursor of aromatic polyamideimide. The aromatic polymer is preferably contained in the composition as a varnish dissolved in a liquid dispersion medium.

[0035] When the composition further contains another resin, the volume concentration of the other resin relative to the total volume of the F particles, the first filler, the second filler and the third filler is preferably 0.1% by volume or more, more preferably 1% by volume or more, and is preferably 15% by volume or less, more preferably 10% by volume or less.

[0036] The composition may be in a powder form, or may further contain a liquid dispersion medium and be in a liquid form. The liquid dispersion medium is preferably a compound that is liquid at atmospheric pressure and 25° C. and has a boiling point of 50 to 240° C. One type of liquid dispersion medium may be used, or two or more types may be used. When two types of liquid dispersion media are used, the two types of liquid dispersion media are preferably compatible with each other.

[0037] The liquid dispersion medium is preferably a compound selected from the group consisting of water, hydrocarbons, amides, ketones and esters. Examples of the hydrocarbon include alicyclic skeleton hydrocarbons such as hexane, heptane, octane, decane, and methylcyclohexane, and aromatic hydrocarbons such as toluene, ethylbenzene, and xylene. Examples of amides include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Examples of the ester include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, and γ-valerolactone.

[0038] When the composition contains a liquid dispersion medium, the content of the liquid dispersion medium is preferably 10% by volume or more, more preferably 20% by volume or more, and is preferably 60% by volume or less, more preferably 50% by volume or less. When the composition contains a liquid dispersion medium, the solid content concentration in the composition is preferably 50% by volume or more. The solid content concentration is preferably 90% by volume or less. The solid content means the total amount (total mass or total volume) of substances that form solid content in a molded product formed from the composition. Specifically, the F polymer (F particles), the first filler, the second filler, and the third filler are solid content, and when the composition contains other resins, the other resins are also solid content, and the total volume concentration of these components is the solid content concentration in the composition.

[0039] The present composition, particularly the present composition containing a liquid dispersion medium, preferably further contains a nonionic surfactant from the viewpoint of improving the dispersion stability of the F polymer (F particles), the first filler, the second filler and the third filler. Examples of the nonionic surfactant include glycol-based surfactants, acetylene-based surfactants, silicone-based surfactants, and fluorine-based surfactants. When the present composition contains a nonionic surfactant, the content of the nonionic surfactant in the present composition is preferably 1 to 15% by volume.

[0040] The present composition may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a dehydrating agent, a plasticizer, a weather resistance agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.

[0041] When the composition contains a liquid dispersion medium and is in a liquid state, the viscosity of the composition is preferably 10 mPa·s or more, more preferably 100 mPa·s or more, and is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. When the present composition contains a liquid dispersion medium and is in a liquid state, the thixotropy ratio is preferably from 1.0 to 3.0.

[0042] The present composition can be obtained by mixing the F polymer (F particles), the first filler, the second filler, and the third filler, and, if necessary, other resins, liquid dispersion media, surfactants, additives, and the like. The composition may be obtained by mixing the F polymer (F particles) with the first filler, the second filler, and the third filler all at once, or may be mixed separately and in order, or a master batch of these may be prepared in advance and mixed with the remaining components. There is no particular restriction on the order of mixing, and the mixing method may be either mixing all at once or mixing in several separate batches. Mixing devices for obtaining the present composition include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.

[0043] As a method for producing the present composition containing a liquid dispersion medium, the first filler, the second filler, and the third filler may be sequentially added to the liquid dispersion medium containing F particles and mixed, which is preferable from the viewpoint of improving the dispersibility of the F particles, the first filler, the second filler, and the third filler. More specifically, the F particles and a part of the liquid dispersion medium are pre-kneaded, and then the first filler, the second filler, and the third filler are sequentially added and further kneaded, and the kneaded mixture obtained is added to the remaining liquid dispersion medium to obtain the present composition. The liquid dispersion medium used in kneading and addition may be the same type of liquid dispersion medium or different types of liquid dispersion medium. Other resins, surfactants, and additives may be mixed during kneading or addition.

[0044] From this composition, a molded product having a thermal conductivity of at least 5 W / m·K can be easily obtained. The thermal conductivity of such a molded product is preferably 10 to 100 W / m·K. The dielectric constant of the molded article obtained from the composition is preferably 2.4 or less, more preferably 2.0 or less, and more preferably greater than 1.0. The dielectric loss tangent of the molded article is preferably 0.0022 or less, more preferably 0.0020 or less, and more preferably greater than 0.0010.

[0045] By subjecting this composition to a molding method such as extrusion, a molded product such as a sheet containing the F polymer, the first filler, the second filler and the third filler can be obtained. When the composition contains a liquid dispersion medium and is in a liquid state, it is preferable to extrude the composition into a sheet. The sheet obtained by extrusion may be further cast by press molding, calendar molding, etc. The sheet is preferably further heated to remove the liquid dispersion medium and to bake the F polymer. When the composition is in powder form, it is preferred to melt extrude the composition, which can be carried out using a single screw extruder, a multi-screw extruder or the like. The composition may also be injection molded to obtain a molded article. When forming a molded product, the present composition may be directly melt extruded or injection molded, or the present composition may be melt kneaded to form pellets, and the pellets may be melt extruded or injection molded to obtain a molded product such as a sheet.

[0046] The thickness of the sheet obtained from the composition is preferably 50 μm or more, more preferably 75 μm or more, and even more preferably 100 μm or more, and preferably 1000 μm or less. The suitable ranges of the thermal conductivity, dielectric constant and dielectric dissipation factor of the sheet are the same as those of the above-mentioned molded product. Note that the thermal conductivity of the sheet means the thermal conductivity in the in-plane direction of the sheet. The linear expansion coefficient of the sheet is preferably 100 ppm / ° C. or less, more preferably 80 ppm / ° C. or less. The lower limit of the linear expansion coefficient of the sheet is 30 ppm / ° C. The linear expansion coefficient means a value obtained by measuring the linear expansion coefficient of a test piece in the range of 25° C. or more and 260° C. or less according to the measurement method specified in JIS C 6471:1995.

[0047] The sheet can be laminated on a substrate to form a laminate. Examples of a method for producing a laminate include a method in which the composition is extruded together with the raw material of the substrate using a co-extruder as the extruder, a method in which the composition is extruded onto the substrate, and a method in which the sheet and the substrate are thermally compressed together. Examples of the substrate include metal substrates such as metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc.; films of preferably heat-resistant resins such as polyester, polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystalline polyester, and tetrafluoroethylene-based polymers; prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates such as silicon carbide, aluminum nitride, and silicon nitride; and glass substrates.

[0048] The shape of the substrate may be flat, curved, or uneven, and may be any of a foil, plate, film, and fiber shape. The ten-point average roughness of the surface of the substrate is preferably 0.01 to 0.05 μm. The peel strength between the sheet and the substrate is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less.

[0049] The composition is placed on the surface of a substrate, and a polymer layer containing the F polymer, the first filler, the second filler, and the third filler is formed, thereby obtaining a laminate having a substrate layer and a polymer layer composed of the substrate. The polymer layer is preferably formed by placing the composition containing a liquid dispersion medium on the surface of the substrate, heating to remove the dispersion medium, and further heating to bake the F polymer. By separating the substrate from the laminate, a sheet containing the F polymer, the first filler, the second filler, and the third filler is obtained. The substrate may be the same as the substrate that can be laminated with the above-mentioned sheet, and the preferred embodiments thereof are also the same.

[0050] Methods for applying the composition include coating, droplet discharging, and immersion, and roll coating, knife coating, bar coating, die coating, and spraying are preferred. The heating for removing the liquid dispersion medium is preferably performed at 100 to 200°C for 0.1 to 30 minutes. In this heating, the liquid dispersion medium does not need to be completely removed, but only needs to be removed to an extent that the layer formed by packing the F particles, the first filler, the second filler, and the third filler can maintain a self-supporting film. In addition, when heating, air may be blown to promote the removal of the liquid dispersion medium by air drying.

[0051] The heating for calcining the F polymer is preferably carried out at a temperature equal to or higher than the calcination temperature of the F polymer, more preferably at 360 to 400° C. for 0.1 to 30 minutes. The heating device for each heating may be an oven or a ventilation drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared rays, etc.). The heating may be carried out under normal pressure or under reduced pressure. The atmosphere during each heating may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.).

[0052] The polymer layer is formed through the steps of disposing the composition and heating. These steps may be performed once each, or may be repeated two or more times. For example, the composition may be disposed on the surface of a substrate and heated to form a polymer layer, and the composition may be disposed on the surface of the polymer layer and heated to form a second polymer layer. In addition, after the composition is disposed on the surface of a substrate and heated to remove the liquid dispersion medium, the composition may be disposed on the surface of the substrate and heated to form a polymer layer. The composition may be disposed on only one surface of the substrate, or on both surfaces of the substrate, in which case a laminate having a substrate layer and a polymer layer on one surface of the substrate layer is obtained, and in which case a laminate having a substrate layer and polymer layers on both surfaces of the substrate layer is obtained.

[0053] Suitable specific examples of the laminate include a metal-clad laminate having a metal foil and a polymer layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and polymer layers on both surfaces of the polyimide film. The preferred ranges of the thickness, thermal conductivity, dielectric constant, dielectric dissipation factor, linear expansion coefficient, and peel strength between the polymer layer and the substrate layer are the same as the preferred ranges of the thickness, thermal conductivity, dielectric constant, dielectric dissipation factor, linear expansion coefficient, and peel strength between the sheet and the substrate in the sheet obtained from the composition described above.

[0054] The composition is useful as a material for imparting insulating properties, heat resistance, corrosion resistance, chemical resistance, water resistance, impact resistance, and thermal conductivity. Specifically, the composition can be used in printed wiring boards, thermal interface materials, substrates for power modules, coils used in power devices such as motors, vehicle engines, heat exchangers, vials, syringes, ampoules, medical wires, secondary batteries such as lithium ion batteries, primary batteries such as lithium batteries, radical batteries, solar cells, fuel cells, lithium ion capacitors, hybrid capacitors, capacitors (aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc.), electrochromic elements, electrochemical switching elements, electrode binders, electrode separators, and electrodes (positive and negative electrodes). The composition is also useful as an adhesive for bonding parts. Specifically, the composition can be used for bonding ceramic parts, metal parts, electronic parts such as IC chips, resistors, and capacitors on substrates of semiconductor elements and module parts, bonding circuit boards and heat sinks, and bonding LED chips to substrates.

[0055] The present invention also relates to a heat dissipation material containing the composition. A specific example of such a heat dissipation material is a thermal interface material (TIM). The TIM containing the composition has high physical properties of the F polymer, the first filler, the second filler, and the third filler, and has excellent mechanical properties and heat resistance, a low linear expansion coefficient, a low dielectric constant, and a low dielectric loss tangent, and is particularly excellent in thermal conductivity. In addition, the surface roughness (Rz) is small, and the adhesiveness is excellent. The composition can be particularly suitably used as a TIM for dissipating large amounts of heat generated from electronic components such as computer chips (CPUs), video graphics arrays, servers, game consoles, smartphones, and LED boards, as well as semiconductor modules including power semiconductors used in electric vehicles and inverters and converters in power transmission systems.

[0056] The present invention also relates to a molded product (hereinafter also referred to as the present molded product) that includes an F polymer, a first filler, a second filler, and a third filler, and the average particle size D1 of the first filler, the average particle size D2 of the second filler, and the average particle size D3 of the third filler satisfy the relationship D1>D2>D3. Details of the F polymer, the first filler, the second filler, and other optional components in the present molded product are the same as those described above in the description of the present composition. The surface roughness Rz of the molded product is preferably 10 μm or less, more preferably 1 μm or less, and is preferably 0.01 μm or more. The molded product is preferably formed from the composition by the method described above, preferably as a sheet. The preferred ranges of the thickness, thermal conductivity, dielectric constant, dielectric loss tangent, linear expansion coefficient, and surface roughness Rz of the sheet are the same as those described above. Such a sheet can be suitably used as a TIM.

[0057] Molded articles such as sheets and laminates formed from the present composition are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sporting goods, food industry products, heat dissipation parts, and the like. Specifically, these include electric wire coating materials (aircraft electric wires, rectangular wires, FFC (Flexible Flat Cable), etc.), enameled wire coating materials used in motors for electric vehicles, etc., power generation coating materials, electrical insulating tapes, insulating tapes for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), carrier films for fuel cells, tape base films for the semiconductor manufacturing process (dicing tape, pick-up tape, etc.), release films for semiconductor molding, liquid crystal antennas, reflectors, transmission lines, COF (Chip on Fuel) base films for electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushes, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food transport belts, etc.), tension ropes, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, chemical and water supply pumps, tools (shovels, files, drills, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, dies, toilets, container coating materials, heat dissipation boards for mounting power devices, heat dissipation parts for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS They are useful as FETs, CPUs, heat dissipation fins, metal heat sinks, blades for wind turbines, wind power generation equipment, and aircraft, housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, and electromagnetic wave shielding.

[0058] Molded articles such as sheets and laminates formed from the present composition are useful as electronic substrate materials such as flexible printed wiring boards and rigid printed wiring boards, protective films and heat dissipating substrates, particularly heat dissipating substrates for automobiles. When using a sheet formed from this composition as a TIM, the sheet may be attached directly to the target substrate, or may be attached to the target substrate via an adhesive layer such as a silicone-based adhesive layer.

[0059] Although the present composition, the heat dissipation material containing the present composition, and the present molded article have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the present composition may have any other optional configuration in addition to the configurations of the above-mentioned embodiments, or may be replaced with any optional configuration that produces a similar effect. EXAMPLES

[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [F Polymer] F particle 1: containing 97.9 mol% of TFE units, 0.1 mol% of NAH units, and 2.0 mol% of PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6 Particles (D50: 2μm) of tetrafluoroethylene polymer (melting temperature: 300℃) with 1000 particles per particle F Particle 2: Particles (D50: 2 μm) of a tetrafluoroethylene polymer (melting temperature: 300 ° C.) having no functional group, containing 98.0 mol % TFE units and 2.0 mol % PPVE units, in that order. [Nitride filler] Boron nitride 1: Product name "HP-40MF100" (manufactured by JFE Mineral Co., Ltd., D50: 36 μm, aggregated structure) [Fillers made of metals or their oxides] Alumina 1: Product name "DAM-20" (manufactured by Denka, D50: 25 μm, spherical) Alumina 2: Product name "CB-P02" (manufactured by Showa Denko, D50: 2 μm, spherical)

[0061] 2. Example of composition production [Example 1] Water, F particles 1, boron nitride 1, alumina 1, and alumina 2 were added in this order, and the mixture was kneaded for 1 minute at 2000 rpm using a planetary centrifugal mixer to obtain composition 1. Composition 1 was in the form of a slurry, and the solid content of composition 1 was 15 volume % of F particles 1, 15 volume % of boron nitride 1, 60 volume % of alumina 1, and 10 volume % of alumina 2. [Examples 2-4] Compositions 2 to 4 were obtained in the same manner as in Example 1, except that the type of F particles and the volume ratios of boron nitride 1, alumina 1 and alumina 2 were changed as shown in Table 1.

[0062] 3. Sheet manufacturing Composition 1 was applied to the surface of a copper foil having a thickness of 0.2 μm using an applicator to form a wet film. Next, the glass substrate on which this wet film was formed was passed through a drying oven at 120° C. for 3 minutes and dried to form a dry film. Furthermore, the copper foil substrate having the dry film was cut to a size of 3 cm x 3 cm, and heat pressed at 340°C and 10 MPa for 3 minutes to obtain a laminate. The peel strength of the resulting laminate was measured by the method described below. The obtained laminate was then immersed in an aqueous solution of ferric chloride for 2 hours to remove the copper foil, thereby obtaining a sheet 1 having a thickness of 150 μm. In the same manner as for Sheet 1, Sheets 2 to 4 were produced from Compositions 2 to 4.

[0063] 4. Evaluation 4-1. Peel strength A test piece measuring 150 mm in length and 10 mm in width was prepared from each laminate. The sheet layer and the copper foil were peeled from one end of the test piece in the longitudinal direction to a position 50 mm from the end, and then a tensile tester was used to measure the maximum load (N / cm) when the sheet layer and the copper foil were peeled at an angle of 90° at a pulling speed of 50 mm / min, and the peel strength was evaluated according to the following criteria. The results are shown in Table 1. [Evaluation criteria for peel strength] ○: Peel strength is over 10 N / cm △: Peel strength is within the range of 5 to 10 N / cm ×: Peel strength is less than 5N / cm

[0064] 4-2. Sheet surface roughness The ten-point average roughness (Rz) was measured in accordance with the specifications in Appendix JA of JIS B 0601:2013.

[0065] 4-3. Thermal conductivity of the sheet A 10 mm × 10 mm square test piece was cut from each sheet, and the thermal conductivity (W / m K) in the in-plane direction was measured at 25°C using a xenon flash analyzer (Netsch, LFA467 HyperFlash). The density required to calculate the thermal conductivity was calculated by dividing the mass by the volume measured with a micrometer. The above results are summarized in Table 1.

[0066] [Table 1]

[0067] As is clear from the above results, the sheets formed from the compositions of the examples satisfying the requirements of the present invention had excellent thermal conductivity, small surface roughness Rz, and excellent adhesion, electrical insulation, and bendability. [Industrial Applicability]

[0068] This composition and the sheets formed from this composition have low surface roughness, and the physical properties of the F polymer and each of the fillers contained therein are highly expressed, resulting in excellent thermal conductivity, heat resistance, and electrical insulation, making them effective for use as heat dissipation materials.

Claims

1. A composition comprising particles of a tetrafluoroethylene-based polymer, a first filler which is a nitride, a second filler which is a metal or an oxide thereof, and a third filler which is a metal or an oxide thereof, wherein an average particle diameter D1 of the first filler, an average particle diameter D2 of the second filler, and an average particle diameter D3 of the third filler satisfy the relationship D1>D2>D3, and the ratio of the average particle diameter of the particles of the tetrafluoroethylene-based polymer to D3 is 2 or less.

2. The composition of claim 1 , wherein the ratio of the average particle size D2 to the average particle size D3 is greater than 2.

3. 2. The composition of claim 1, wherein the tetrafluoroethylene-based polymer is a heat-fusible tetrafluoroethylene-based polymer having oxygen-containing polar groups.

4. 2. The composition according to claim 1, wherein the average particle size of the particles of the tetrafluoroethylene-based polymer is 0.1 to 6 μm.

5. 2. The composition according to claim 1, wherein the first filler is an aggregate of scaly primary particles of boron nitride, and the average particle size D1 of the aggregate is 25 to 75 μm.

6. 2. The composition of claim 1, wherein the second filler is aluminum oxide and the average particle size D2 is 10 to 40 μm.

7. 2. The composition of claim 1, wherein the third filler is aluminum oxide and the average particle size D3 is less than 10 μm.

8. The composition of claim 1 , wherein the second filler and the third filler are both spherical.

9. The composition according to claim 1, wherein the content of the tetrafluoroethylene-based polymer particles is 10 to 30 vol%, the content of the first filler is 5 to 30 vol%, the content of the second filler is 50 to 80 vol%, and the content of the third filler is 5 to 30 vol%, relative to the total amount of the tetrafluoroethylene-based polymer particles, the first filler, the second filler, and the third filler.

10. The composition of claim 1 further comprising a liquid dispersion medium.

11. A heat dissipating material comprising the composition according to any one of claims 1 to 10.

12. A method for producing a molded article, comprising extruding the composition according to any one of claims 1 to 10 or disposing it on a surface of a substrate to obtain a molded article comprising the tetrafluoroethylene-based polymer, the first filler, the second filler, and the third filler.

13. A molded article comprising a tetrafluoroethylene-based polymer, a first filler which is a nitride, a second filler which is a metal or an oxide thereof, and a third filler which is a metal or an oxide thereof, wherein an average particle diameter D1 of the first filler, an average particle diameter D2 of the second filler, and an average particle diameter D3 of the third filler satisfy the relationship D1>D2>D3.

14. The molded article according to claim 13, having a thickness of 100 μm or more.

15. The molded product according to claim 13 or 14, having a surface roughness Rz of 25 μm or less.

16. The molded product according to claim 13 or 14, having a thermal conductivity of 5 W / m·K or more.

Citation Information

Patent Citations

  • Thermally conductive resin composition and molding thereof

    JP2022026651A

  • Insulation resin sheet, laminate, and semiconductor device

    JP2023033211A

  • Heat dissipation sheet and heat dissipation sheet-equipped device

    WO2019065146A1